THE EFFECT OF WORK DISCIPLINE AND WORK ABILITY ON EMPLOYEE PERFORMANCE AT PT. PLN (PERSERO) RAYON MEDAN SELATAN - Rini Astuti; Nanda Nur Pratama (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
The purpose of this research is  to find out and analyze the effect of work discipline on employee performance, to find out and analyze the effect of work ability on employee performance and to find out and analyze the effect of work discipline and work ability on employee performance at PT. PLN (Persero) Rayon South Medan. In this research on approach used through an associative approach. The sample used in this research is saturated sampling teachnique, where the entire population is sampled. The data collection techniques used in the research are questionnaires and data analysis teaches using SPSS (Statistical Package For The Social Sciences). to test the three hypotheses advanced in the research. research shous that the effect of work discipline and work ability on employee performance.